2015
DOI: 10.1093/nar/gkv680
|View full text |Cite
|
Sign up to set email alerts
|

UV induced ubiquitination of the yeast Rad4–Rad23 complex promotes survival by regulating cellular dNTP pools

Abstract: Regulating gene expression programmes is a central facet of the DNA damage response. The Dun1 kinase protein controls expression of many DNA damage induced genes, including the ribonucleotide reductase genes, which regulate cellular dNTP pools. Using a combination of gene expression profiling and chromatin immunoprecipitation, we demonstrate that in the absence of DNA damage the yeast Rad4–Rad23 nucleotide excision repair complex binds to the promoters of certain DNA damage response genes including DUN1, inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…It has previously been established that the enhanced rate of repair in ORFs is due to the combined activity of GG-NER and TC-NER operating on actively transcribing strands (Hu et al 2015). To examine this, we analyzed CPD repair rates in the 15% of the lowest expressed or silent genes in the genome, as defined by global gene expression data for wildtype cells (Zhou et al 2015). Supplemental Figure S1B shows that these genes have little or no enhanced rates of repair in ORFs.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been established that the enhanced rate of repair in ORFs is due to the combined activity of GG-NER and TC-NER operating on actively transcribing strands (Hu et al 2015). To examine this, we analyzed CPD repair rates in the 15% of the lowest expressed or silent genes in the genome, as defined by global gene expression data for wildtype cells (Zhou et al 2015). Supplemental Figure S1B shows that these genes have little or no enhanced rates of repair in ORFs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many of the gene regulatory DNA sequences reported to associate with Rad4/XPC possess a GGG-containing consensus sequence. In the study by Reed and colleagues, Rad4-Rad23 was shown to associate with STRE (Stress Response Element) promoter in the absence of UV light to regulate the transcription of several DNA damage repair signaling genes in yeast (52). The STRE elements are present in the upstream region of many genes, induced under various stress conditions such as osmotic pressure, oxidative stress and heat and contain a run of G's (AGGGG) (53,54).…”
Section: Implications Of C/g-rich Sequences Several Studies Have Impmentioning
confidence: 99%
“…To confirm this, we analysed CPD repair rates in the 15% of genes being expressed at the lowest levels in the genome. We recently reported global gene expression data in wild-type cells either in untreated or irradiated with UV (Zhou et al 2015). We identified the genes expressing the lowest levels of transcription following UV damage and plotted the relative rates of CPD repair in these genes and compared these repair rates to the rates observed in the remaining 85% of the genome.…”
Section: The Gg-ner Complex Promotes Efficient Repair Of Uv-induced Dmentioning
confidence: 99%